Clinical significance of different carnitine levels for improving the prognosis of patients undergoing hemodialysis. (25th November 2016) - Zhang, Yu-Mei; Zhuo, Li; Hu, Jing; Cui, Gang; Zhang, Ling; Zhang, Xiang-Lin; Li, Wen-Ge
Abstract: Objective: To investigate plasma-free carnitine (Fc), acylcarnitine (Ac), and total carnitine (Tc) levels in patients undergoing hemodialysis (HD), and to explore their clinical significance. Methods: A total of 20 subjects were in the normal control group and 133 patients undergoing HD were divided into medicated (received carnitine treatment) and non-medicated groups. The medicated group was further divided into three subgroups according to Fc level: Fc = 80–199, 200–299, and ≥ 300 μmol/L. We used non-derivative tandem mass spectrometry to determine carnitine levels, and clinical symptoms such as weakness, hypotension, and muscle cramps were recorded during dialysis. Results: Fc and Tc levels were significantly lower in the non-medicated group than in the control group, whereas Fc, Ac, and Tc levels were higher in the medicated than non-medicated group ( p<  .05). The medicated group had fewer symptoms during dialysis than the non-medicated group such as weakness, hypotension, and muscle cramps ( p<  .05). An additional comparison showed that the incidence rates of hypotension and muscle cramps in the Fc < 80–199 μmol/L group were significantly lower than those in the Fc ≥ 300 μmol/L medicated and non-medicated groups. Conclusions: Patients undergoing HD have low carnitine levels.l -Carnitine can effectively increase Fc concentration and improve clinical symptoms; however, only the proper Fc range can reduce complications caused by dialysis. Thus, this range needs to be determined.